PENGARUH PENYIMPANAN PADA SUHU RENDAH TERHADAP UMUR SIMPAN DAN TOTAL BAKTERI AIR SUSU IBU ( ASI ) - Aminah, Siti; Isworo, Joko Teguh (Universitas Muhammadiyah Semarang, 2004)
Mother's milk is a fat emulsion in protein, lactose and organic salts which is secreted by both mother bosom gland, as especialis food to baby. Giving of mother's milk until 4 month of the baby's age ( exclusive ASI) have fulfilled requirement of food to baby. To mothers work, giving of exclusive ASI (mother's milk) is unworkable properly.One of the alternative to be able to give ASI fully by conducting of storage ASI at low tentperoture. Results of research indicated that there was change which striking at colour, flronta, acidity (pH) and consistency up to the fourth days of storage. Change of cotrsistency and aroma happened at the fifth days of storage, this matter showed that the duration of storage of ASI at the low temperature is 4 day. Analysis to total of bacteria indicated that the duration of storage do not have an effect on total of bacteria of ASI kept.